Sanitation Knowledge and Hygiene Practices: An Evaluation of Indonesian Online Food SMEs Based on National Food Safety Guidelines - Ridawati; Alsuhendra; Muhammad Indera Ramadani (Postgraduate, University of Mataram, 2023)
In Indonesia, the surge in online food Small and Medium Enterprises (SMEs) has underscored the critical need for stringent sanitation and hygiene practices. Utilizing a cross-sectional approach, the research assessed knowledge levels through a questionnaire, complemented by an evaluative tool aligned with guidelines from the Indonesian food and drug regulatory authority. From a sample of 132 SMEs spanning various Indonesian cities and regencies, it was observed that 57.6% had an adequate grasp of sanitation principles. Furthermore, a significant correlation between knowledge and its practical application emerged. Notably, there was a discernible difference in practice scores between participants with limited knowledge compared to those with a deeper understanding, evidenced by a mean difference of 10.62Â±3.77. This highlights a substantial inconsistency in translating knowledge into practice. Despite a reasonable level of awareness, the practical execution of sanitation and hygiene standards remains uneven among these enterprises. This gap indicates a need for focused interventions to enhance the consistent application of sanitation practices in the Indonesian online food SME industry, ensuring better compliance with established hygiene standards.